Muslim friendly hospitality services-requirements (MS 2610:2015) - Ramli, Noriah (Department of Standards Malaysia, 2015)
The Muslim Friendly Hospitality Services (MFHS) standard is Malaysia’s first standard dedicated for the Islamic tourism sector. Initiated and led by NRGS130010001 Research Team of the International Islamic University Malaysia (IIUM),the original submission to develop the standard was made in December 2012 to the Department of Standards Malaysia (DSM). later followed by the appointment of SIRIM as the standard’s secretariat by DSM and the formation of draft committee by the Technical Committee (TC) on Management System from Islamic Perspectives. The drafting committee of the standard comprises main representatives of tourism industry players including Islamic Tourism Centre (ITC), Tourism Malaysia, Malaysia Association of Hotel Owners (MAHO), Malaysia Association of Hotel (MAH), Malaysia Association of Tour and Travel Agents (MATTA), Bumiputera Travel and Tour Agents Association of Malaysia (Bumitra) and Malaysian Tourist Guides Council (MTGC).After months of developing, drafting and revising the document was released as “Draft Malaysian Standard : Muslim Friendly Hospitality Services – Requirements” for a two-month public comment commencing 1 August 2014 until 30 September 2014. The MS2610:2015 was published in February 2015.